Lifestyled : your guide to a more organized & intentional life - Gill, Shira, 1977- (Ten Speed Press, 2024)
This guide offers realistic strategies to improve sleep, nutrition, and wellness by implementing simple habits and routines. It encourages creating a home that feels good, fostering meaningful relationships, and redefining success based on personal values. It also helps align financial strategies with those values, prioritize energizing activities, and disrupt unproductive thought patterns to build motivating new narratives.